O-199 Couples presenting to Infertility clinics - Are they really infertile?. (30th June 2022) - Khoja, K; Dasgupta, S; Frodsham, L.C.G; Patra, P; Chanda, A; Yap, T
Abstract: Study question: Are couples presenting to infertility clinics actually infertile, or is there an undiagnosed underlying sexual dysfunction whose treatment can lead to natural conception avoiding the need for assisted reproductive techniques? Summary answer: All couples presenting with infertility should be asked about sexual function. If sexual dysfunction is diagnosed, a signicant proportion can achieve pregnancy without assisted reproduction What is known already: Infertility is defined as the inability to conceive after one year of frequent and regular unprotected sexual intercourse (SI). Although sexual histories are a key part of primary care screening guidelines for infertility, they are often overlooked during the infertility work-up. It is postulated that a large proportion of couples presenting to infertility clinics have underlying sexual dysfunction. Treatment through specialist counselling for couples with sexual dysfunction can help achieve pregnancy, negating the need for complex assisted reproductive techniques such as intravaginal insemination (IVI) and intrauterine insemination (IUl). Study design, size, duration: 108 couples were recruited from a national fertility clinic. The duration of the study was 3.5 years, from January 2016 to August 2019. The study was based primarily on surveys, where diagnostic work-up for infertility included tools for measuring sexual dysfunction, such as the IIEF-15 questionnaire. Our objectives were to find the extent of improvement of SI before and after specialist referral, and the time to conceive (TTC) in those with and without sexual dysfunction. Participants/materials, setting, methods: Couples who never had successful completion of SI (despite producing an ejaculate sample) prior to clinic attendance were included. Treatment via specialist referral was then offered to these patients. Data were analysed to compare outcomes between those who subsequently had successful SI ("Group A") and those who had not had successful SI ("Group B"). Both groups were counselled for fertility treatments, such as IVI and IUI. TTC between the groups was analysed using Kaplan-Meier analysis Main results and the role of chance: Out of 2057 couples presenting to the Infertility Clinic, 128 (5.98%) had never had successful SI. From this, 108 couples were included in the study. Two-thirds of couples revealed sexual difficulties at the beginning of the initial consultation. In men, erectile dysfunction was the predominant cause (70.4%, n = 76). In women, dyspareunia was the leading problem (18.2%, N = 20). Fertility investigations, which included hormone profiles, revealed normal results in most cases. Treatment via referral to specialist sexual counselling was offered to all couples. Only 33 couples reported successful SI during subsequent visits (Group A). 13 of these 33 couples went on to conceive (11 naturally, 1 by IUI and 1 by IVI). The rest (n = 75), who had no improvement (Group B), had a significantly longer duration of sexual dysfunction, which was also more severe. Out of these 75 couples, 8 conceived (0 naturally, 6 by IVI, and 2 by IUI).The IIEF-15 scores (index for sexual dysfunction) between groups A and B were 10.72 ± 4.28 vs. 8 ± 4.73, P-value 0.0142. Group A couples (less severe sexual dysfunction) conceived earlier than Group B (mean duration 27.2 weeks vs. 48.8 weeks log-rank P value <0.001). Limitations, reasons for caution: The main limitations of this study include a small sample size and a small minority of couples refusing to undergo specialist counselling despite having sexual difficulties as they were only interested in assisted reproductive interventions such as IUl and IVI. These limitations hinder the internal/external validity of the study. Wider implications of the findings: All couples presenting with infertility should be asked about sexual function. If sexual dysfunction is diagnosed, a signicant proportion can be helped to achieve pregnancy without assisted reproduction. In the cases of couples with persistent sexual difficulty, assisted reproductive techniques like IUI and IVI give a reasonable pregnancy rate. Trial registration number: Not applicable